2019
DOI: 10.1177/1934578x19844133
|View full text |Cite
|
Sign up to set email alerts
|

Alkaloids From Zanthoxylum nitidum and Their Cytotoxic Activity

Abstract: Zanthoxylum nitidum (Roxb.) DC (Rutaceae) is a traditional medicine used for the treatment of various diseases like toothache, gingivitis, fever, colic vomiting, diarrhea, and cholera. Three new alkaloids, zanthocadinanine C (1), 7-methoxy-8-demethoxynitidine (2), and zanthonitiside I (3) were isolated from the stems and twigs of Z. nitidum. Their structures were determined on the basis of extensive spectroscopic, including 1-dimensional and 2-dimensional nuclear magnetic resonance and mass spectroscopy data. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 17 publications
0
6
0
Order By: Relevance
“…Zanthocadinanine C (70) and 7-methoxy-8-demethoxynitidine (71) exhibit cytotoxic activity against five human cancer cell lines KB, MCF-7, LNCaP, HepG-2, and lu-1, whereas the alkaloid 7-methoxy-8-demethoxynitidine (71) has high activity with IC50 values from 10.3 to 12.6 µM. Furthermore, zanthocadinanine C ( 70) is less active with IC50 > 100 µM [98]. Dihydronitidine (72) (Figure 23), a benzophenanthridine alkaloid, is isolated from Zanthoxylum.…”
Section: -Acetonyldihydrochelerythrine (67)mentioning
confidence: 99%
See 2 more Smart Citations
“…Zanthocadinanine C (70) and 7-methoxy-8-demethoxynitidine (71) exhibit cytotoxic activity against five human cancer cell lines KB, MCF-7, LNCaP, HepG-2, and lu-1, whereas the alkaloid 7-methoxy-8-demethoxynitidine (71) has high activity with IC50 values from 10.3 to 12.6 µM. Furthermore, zanthocadinanine C ( 70) is less active with IC50 > 100 µM [98]. Dihydronitidine (72) (Figure 23), a benzophenanthridine alkaloid, is isolated from Zanthoxylum.…”
Section: -Acetonyldihydrochelerythrine (67)mentioning
confidence: 99%
“…Benzophenanthridine alkaloids 8-methoxynorchelerythrine (90), 11-demethylrhoifoline B (91), 8-methoxynitidine (92), 8-acetylnorchelerythrine (93), 8,9,10,12-tetramethoxynorchelerythrine (94), isointegriamide (95), pancorine (96), 8-methoxychelerythrine (97), oxynitidine (98), and oxysanguinarine (99) (Figure 28) are extracted from Toddalia asiatica. Studies have shown that the above compounds could inhibit eight types of human tumor cell lines in vitro, including A549 (human lung cancer), BGC-823 (human gastric cancer), HCT-15 (human colon cancer), Hela (human cervical cancer), HepG2 (human liver cancer), MCF-7 (human breast cancer), SK-MEL-2 (human skin cancer), and SGC-7901 (human gastric cancer).…”
Section: Antitumor Activities Of Benzopheridine Alkaloid From Toddaliamentioning
confidence: 99%
See 1 more Smart Citation
“…In daily life, ZN could be used as toothpaste and hand sanitizer. In a previous study, researchers were mainly focused on the chemical isolation and activity evaluation of ZN ( Yang et al, 2008 ; Zhao et al, 2018 ; Nguyen et al, 2019 ). ZN extracts showed good anti-inflammatory and antioxidant activities ( Xie, 2000 ; Liu et al, 2014 ).…”
Section: Introductionmentioning
confidence: 99%
“…Phytochemical investigations showed the presence of alkaloids, flavonoids, and true amino acids in the bark of Zanthoxylum nitidum (Bhattacharya & Zaman, 2009). These compounds have benefits as anti-viral, antiinflammatory, antioxidant, and anti-cancer activities (Van Nguyen et al, 2019).…”
Section: Introductionmentioning
confidence: 99%